Reforming the Treatment of Minority Shareholdings in the EU: Making the Problem Worse Instead of Better? - (:unkn) unknown (KLUWER LAW INT, 2015)
This article considers the treatment of non-controlling shareholdings in EU competition law, which has received increased attention following the Ryainair/Aer Lingus case. The Commission perceived this case to illustrate the existence of an enforcement gap and put forward possible solutions in its recent White Paper. Irrespective of whether there is actually a loophole as pronounced, these solutions generally focus on the future inclusion of non-controlling shareholdings in the Merger Regulation. However, they are possibly inconsistent with the rules of EU competition law governing other operations, especially joint ventures. Therefore, such a reform may lead to some inconsistencies and uncertainties and thereby further complicate the current situation in the EU, instead of improving it. This article thus argues that under the current framework of EU competition law, more active use of the current competition tools, particularly Article 101 TFEU, is a better way to solve the under-enforcement problem regarding non-controlling shareholdings.
Keywords: CORPORATE EQUITY OWNERSHIP